Lead apron leak test at the Padang Reksodiwiryo Army Hospital's radiology installation - Yori Rahmadianti; Sagita Yudha; Nerifa Dewilza; Livia Ade Nansih; Tasya Ramadanti (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2023)
A lead apron is a lead apron designed to protect the body from radiation hazards. The lead apron test is carried out once a year to ensure that it can provide optimal protection when in use, it is necessary to test personal protective equipment. Based on observations, the storage and placement of tin aprons is not in accordance with the rules so that it can reduce its function as personal protective equipment. This study aims to determine whether there is a leak in the lead apron, and to find out whether the lead apron is still suitable for use as personal protective equipment (PPE). This type of quantitative research with experimental methods at the Radiology Installation of RST Dr. Reksodiwiryo Padang on March 31, 2022. The sample in this study was 2 lead aprons, each lead apron is divided into four quadrants, namely the upper right side, upper left side, lower right side and lower left side. Each quadrant was tested with a tube voltage of 70 Kv and a current of 16 mAs. Then made observations and compared with the theory of Lambert and Mc Keon. The results of the study found that there was a leak in the Apron A quadrant 3 with an area of ​​0.75 mm2 and quadrant 4 with an area of ​​0.67 mm2. On Apron B there is a leak in quadrant 4 with an area of ​​0.06 mm2. From the results of the study of lead apron leaks in quadrant 3 and quadrant 4, the quadrant area is a critical area which according to Lambert's theory should not exceed 15 mm2 so that the lead apron under study is still suitable for use as personal protective equipment (PPE).